Effects of crude humin and compost produced from selected waste on Zea mays growth, nutrient uptake and nutrient use efficiency - Perumal, Palanivell; Kasim, Susilawati; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Academic Journals, 2013)
Waste from oil palm plantations, paddy fields, sawn timber and poultries are substantial. Inappropriate disposal of these wastes can cause environmental problems such as air and land pollutions. The objective of this study was to determine the effect of crude humin and compost produced from rice straw, rice husk, sawdust, and oil palm empty fruit bunch on growth, dry matter production, nutrient uptake and nutrient use efficiency of maize. Standard procedures were used to determine soil pH, total nitrogen, exchangeable ammonium, available nitrate, exchangeable phosphorus, cations, organic matter, total organic carbon and cation exchange capacity before and after planting. The plants were measured for diameter and height at tasselling stage prior to harvest. Dry matter production, nutrient uptake and nutrient use efficiency were also determined. Application of sawdust compost (T8) significantly increased maize plant diameter, height, dry matter production, and N, P and K uptake and use efficiency. It also reduced N, P and K based chemical fertilizer up to 90%. Application of humin and other selected waste composts (T6, T7 and T9) could be used as alternative for chemical fertilizers and their similar effects on maize plants.